Graphite and preparation method and application thereof

By using new graphite materials in lithium-ion batteries, combining large particle size and low graphitization characteristics, the deterioration of dynamic performance and side reaction problems of lithium-ion batteries are solved, and the cycle performance and life of the battery are improved.

CN119240684APending Publication Date: 2025-01-03JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411228833.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the process of increasing the energy density of existing lithium-ion batteries, the dynamic performance deteriorates, making it difficult to take into account both high energy density and high kinetic performance. The side reactions of graphite during the charging and discharge cycle lead to deterioration of the cell cycle performance, affecting the life.

Method used

Develop a new graphite material, which can reduce side reactions by increasing particle size and reducing graphitization by using large-particle single particle morphology, increase the spacing of graphite layers, improve graphite dynamics, and improve cell circulation. Performance and prolong life.

Benefits of technology

By balancing the particle size and graphitization characteristics of graphite, the side-reactivity sites are reduced, the lithium ion deintercalation kinetics are improved, the kinetics of negative electrode sheets are improved, the battery cycle performance and the life span are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240684A_ABST
    Figure CN119240684A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage, in particular to graphite and a preparation method and application thereof. Therefore, when the negative electrode plate is applied to a battery, the cycle performance of the battery can be improved, and the service life of the battery can be prolonged. A graphite having a D50 of 8 [mu] m to 35 [mu] m and a single-peak or double-peak peak pattern in particle size distribution; the graphitization degree of the graphite is GD, the GD ranges from 88% to 95%, and the GD / D50 ranges from 2.6% to 11.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to graphite and a preparation method and application thereof. Background Art

[0002] With the rapid increase in the share of clean energy such as wind and solar power generation, the demand for storage in wind and solar power stations is also rapidly increasing. With the development of secondary batteries, the market has put forward higher and higher requirements for the energy density of secondary batteries. However, the increase in energy density will also lead to the degradation of the dynamic performance of secondary batteries. From a technical perspective, it is difficult to achieve perfect compatibility between high energy density and high dynamic performance.

[0003] The lifespan of conventional photovoltaic or wind power generation can reach 20 to 30 years. In order to ensure that the energy storage power station can meet the application requirements of wind and solar power stations throughout the entire life cycle, it is imperative to develop ultra-long-life energy storage cells. Summary of the invention

[0004] In view of the above problems, the present invention provides a new type of graphite material with good dynamic performance. When used in negative electrode plates, the dynamic performance of the negative electrode plates can be improved. When used in batteries, the cycle performance of the batteries can be improved and the life of the batteries can be extended.

[0005] The technical solution is as follows:

[0006] A graphite, whose D50 is 8 μm to 35 μm, and whose particle size distribution has a single peak or a double peak;

[0007] The graphite has a graphitization degree of GD, GD is 88% to 95%, and GD / D50 is 2.6% to 11.5%.

[0008] In some embodiments, GD / D50 is 3.0% to 5.5%.

[0009] In some embodiments, the graphitization degree of the graphite is negatively correlated with its particle size.

[0010] In some embodiments, the particle size distribution of the graphite is a unimodal normal distribution, and the D10 of the graphite is 10 μm to 15 μm, the D50 is 25 μm to 29 μm, and the D90 is 40 μm to 50 μm.

[0011] In some embodiments, the particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5):(5-9);

[0012] The graphite has a D10 of 6 μm to 8 μm, a D25 of 8 μm to 12 μm, a D50 of 12 μm to 20 μm, a D75 of 20 μm to 40 μm, and a D90 of 40 μm to 50 μm.

[0013] In some embodiments, the particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5):(5-9);

[0014] The graphite has a D10 of 6 μm to 8 μm, a D25 of 8 μm to 10 μm, a D50 of 10 μm to 15 μm, a D75 of 15 μm to 30 μm, and a D90 of 30 μm to 50 μm.

[0015] The present invention also provides a method for preparing the graphite as described above, comprising the following steps:

[0016] The mixed material of the carbon source, the catalyst, the conductive agent and the binder is subjected to molding treatment to prepare a solid composite;

[0017] The solid composite is graphitized, and the graphite is prepared by controlling the graphitization temperature and time.

[0018] It can be understood that the pressure of the molding treatment, the temperature and time of the graphitization treatment described in the present invention can be reasonably set according to actual conditions. All molding treatment pressures, graphitization treatment temperatures and times that can obtain the above-mentioned graphite are within the protection scope of the present invention and are not specifically limited here.

[0019] Optionally, the pressure of the above-mentioned molding treatment is 150MPa-250MPa, the temperature of the graphitization treatment is 2500°C-3000°C, and the time is 15h-50h.

[0020] It can be understood that the carbon source, catalyst, conductive agent and binder described in the present invention are conventionally used in the preparation of graphite in the art, and no requirement is made therefor.

[0021] Optionally, the carbon source is coke raw material, the catalyst is ferroferric oxide, the conductive agent is conductive carbon black, and the binder is asphalt.

[0022] Similarly, the conductive agent used to prepare graphite in the present invention is the conductive agent conventionally used to prepare graphite in the art, and no requirement is made for this. Optionally, the conductive agent used to prepare graphite is conductive carbon black.

[0023] Similarly, the binder used to prepare graphite in the present invention is a binder conventionally used to prepare graphite in the art, and no requirement is made for this. Optionally, the binder used to prepare graphite is asphalt.

[0024] The present invention also provides a negative electrode active material, which includes the graphite as described above.

[0025] The present invention also provides a negative electrode plate, which comprises a negative electrode current collector and a negative electrode active layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active layer comprises the graphite as described above, or the negative electrode active material as described above.

[0026] In some embodiments, the negative electrode active layer further includes a negative electrode conductive agent and a negative electrode binder;

[0027] In terms of mass percentage, the active layer includes 85% to 98% of the negative electrode active material, 0.5% to 10% of the negative electrode conductor, and 1.5% to 5% of the negative electrode binder.

[0028] In some embodiments, the negative electrode conductive agent includes at least one of carbon nanotubes, carbon nanofibers, conductive graphite, graphene, acetylene black and carbon black.

[0029] In some embodiments, the negative electrode binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and polyacrylate.

[0030] The present invention also provides an energy storage device, which includes the graphite as described above, or includes the negative electrode active material as described above, or includes the negative electrode plate as described above.

[0031] The present invention also provides an electrical equipment, which comprises the energy storage device as described above, and the energy storage device supplies power to the electrical equipment.

[0032] The present invention has at least the following beneficial effects:

[0033] Research has found that (1) single-particle artificial graphite will lead to graphite deintercalation of lithium due to the reduction of electrochemically active specific surface area, and the reaction kinetics will deteriorate. During long-cycle applications, the overall kinetics of the battery cell will gradually decrease. Single-particle artificial graphite will have a greater risk of insufficient kinetic lithium precipitation in the middle and late stages of the cycle due to poor kinetics; (2) high-graphitization graphite crystals have high order, and the graphite interlayer spacing is lower than that of conventional graphitization graphite. During the process of cyclic deintercalation of lithium, the graphite flakes are more easily destroyed, resulting in graphite structure collapse and capacity decay. On the one hand, the present invention increases the particle size of graphite and uses large-size single-particle morphology to reduce side reactions. On the other hand, by reducing the degree of graphitization, the graphite interlayer spacing is increased, the energy barrier of lithium ion deintercalation process is reduced, and the graphite kinetics are improved, thereby solving the problem of kinetic deterioration caused by large-size single-particle morphology.

[0034] It can be seen that the present invention complements the advantages of the two characteristics of large graphite particle size morphology and low graphitization degree, greatly reducing the active sites of side reactions on the graphite surface, and improving the dynamics of graphite lithium extraction by increasing the graphite interlayer spacing. When used for negative electrode sheets, it can improve the dynamic performance of negative electrode sheets, and then used for batteries, it can improve the cycle performance of batteries and extend the life of batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The graphite particle size distribution diagram of Examples 1 to 4 of the present invention and Comparative Example 1;

[0036] Figure 2 The battery cycle performance results shown in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0037] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0039] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0040] The words "preferably", "more preferably", "preferably", "better", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the statement of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention. That is, in the present invention, "preferably", "more preferably", "preferably", "better", etc. are only used to describe implementation methods or examples with better effects, but do not constitute a limitation on the scope of protection of the present invention.

[0041] In the present invention, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.

[0042] In the present invention, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multilayer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present invention, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0043] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0044] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0045] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0046] In the present invention, "above" or "below" includes the number itself. For example, "below 1" includes 1.

[0047] With the development of lithium-ion batteries, the market has put forward higher and higher requirements for the energy density of lithium-ion batteries. However, the increase in energy density will also lead to the deterioration of the dynamic performance of lithium-ion batteries. From a technical perspective, it is difficult to achieve perfect compatibility between high energy density and high dynamic performance.

[0048] As one of the four key main materials for energy storage cells, graphite has a crucial impact on the cycle life of the cells. Studies have found that the lithium consumption caused by the side reactions of graphite during the charge and discharge cycle is the main reason for the deterioration of the cycle performance of the cells. Therefore, reducing the side reactions of graphite during the charge and discharge cycle is the key entry point for improving the life of the cells. Based on this, the present invention provides a new type of graphite material with good kinetic properties and an ultra-long cycle life. Using it for the negative electrode plate can improve the kinetic properties of the negative electrode plate, and then using it for batteries is beneficial to take into account the energy density and kinetic performance of the battery, and can reduce the side reactions during the cycle, improve the cycle performance of the battery, and extend the life of the battery.

[0049] The technical solution is as follows:

[0050] A graphite, whose D50 is 8 μm to 35 μm, and whose particle size distribution has a single peak or a double peak;

[0051] The graphite has a graphitization degree of GD, GD is 88% to 95%, and GD / D50 is 2.6% to 11.5%.

[0052] On the one hand, the present invention increases the particle size of graphite and reduces side reactions by using the large-size single particle morphology. On the other hand, the graphite interlayer spacing is increased by reducing the degree of graphitization, the energy barrier of the lithium ion deintercalation process is reduced, and the graphite dynamics is improved, thereby solving the problem of dynamic deterioration caused by the large-size single particle morphology.

[0053] It can be understood that in the present invention, the D50 of graphite is 8μm to 35μm, including but not limited to 8μm, 10μm, 12μm, 14μm, 15μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm, 26μm, 28μm, 30μm, 32μm, 34μm or 35μm.

[0054] It can be understood that in the present invention, the peak type of the graphite particle size distribution is unimodal, such as normal distribution, or the peak type of the graphite particle size distribution is bimodal, non-normal distribution.

[0055] Without limitation, the present invention tests the particle size distribution of graphite by using a laser particle size analyzer LA-960V2, using water as a medium, and using mechanical force to disperse and test the agglomerated particles, and taking the average of three test results. The original data of the particle size distribution is imported into the drawing software, and the peak area of ​​each part is calculated by the peak fitting method.

[0056] It can be understood that in the present invention, the graphitization degree of the graphite is GD, and GD is 88% to 95%, including but not limited to 88%, 88.2%, 88.4%, 88.6%, 88.8%, 89%, 89.2%, 89.4%, 89.6%, 89.8%, 90%, 90.2%, 90.4%, 90.6%, 90.8%, 91%, 91.2%, 91.4%, 91.6%, 91.8%, 92%, 92.2%, 92.4%, 92.6%, 92.8%, 93%, 93.2%, 93.4%, 93.6%, 93.8%, 94%, 94.2%, 94.4%, 94.6%, 94.8% or 95%. Further, in some embodiments, the GD of the graphite is 88% to 90%.

[0057] It is understandable that in the present invention, GD / D50 is 2.6% to 11.5%, including but not limited to 2.6%, 2.7%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5%, 8.8%, 9.0%, 9.2%, 9.5%, 9.8%, 10.0%, 10.2%, 10.5%, 10.8%, 11.0%, 11.2% or 11.5%. Further, in some embodiments, GD / D50 is 3% to 5.5%.

[0058] In some of the embodiments, the graphitization degree of the graphite is negatively correlated with its particle size, such that the graphitization degree decreases with increasing particle size, thereby reducing side reactions, reducing the energy barrier of lithium ion deintercalation and insertion, and improving graphite kinetics, thereby solving the problem of kinetic deterioration caused by large-size single particle morphology.

[0059] (1) In some embodiments, the particle size distribution of the graphite is a unimodal normal distribution, the D10 of the graphite is 10 μm to 15 μm, the D50 is 25 μm to 29 μm, and the D90 is 40 μm to 50 μm. Furthermore, the GD of the graphite is 88% to 90%.

[0060] (2) In some embodiments, the particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5):(5-9); the D10 of the graphite is 6 μm-8 μm, D25 is 8 μm-12 μm, D50 is 12 μm-20 μm, D75 is 20 μm-40 μm, and D90 is 40 μm-50 μm.

[0061] It can be understood that for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is (1-5): (5-9), including but not limited to 1:9, 2:8, 3:7, 4:6 or 5:5. Further, for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is (2-5): (5-8). Further, for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is 2:8 or 5:5. Further, the GD of the graphite is 88% to 90%.

[0062] (3) In some embodiments, the particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5):(5-9); the D10 of the graphite is 6 μm-8 μm, D25 is 8 μm-10 μm, D50 is 10 μm-15 μm, D75 is 15 μm-30 μm, and D90 is 30 μm-50 μm.

[0063] It can be understood that for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is (1-5): (5-9), including but not limited to 1:9, 2:8, 3:7, 4:6 or 5:5. Further, for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is (2-5): (5-8). Further, for the graphite, the peak area ratio of the first peak to the second peak of its particle size distribution is 1:9. Further, the GD of the graphite is 88% to 90%.

[0064] In some embodiments, the specific surface area of ​​the graphite is 1m 2 / g~5m 2 / g.

[0065] It can be understood that by controlling the specific surface area of ​​the graphite within the above range, the side reaction active sites can be reduced, thereby improving the cycle performance of the battery and extending the life of the battery.

[0066] The present invention also provides a method for preparing the graphite as described above, comprising the following steps:

[0067] The mixture of coking raw material, ferroferric oxide, conductive carbon black and asphalt is subjected to molding treatment to prepare a solid composite;

[0068] The solid composite is graphitized, and the graphite is prepared by controlling the temperature and time of the graphitization treatment.

[0069] Through the molding process, the raw materials are tightly bonded together, and combined with the graphitization treatment, the non-graphite carbon is physically changed under the action of high temperature, so that the hexagonal carbon atom plane network layer stacking structure is perfected and developed, and it is transformed into graphite carbon / graphite microcrystals with a three-dimensional regular and ordered structure of graphite. By controlling different graphitization treatment times, graphites with different porous structures and different graphitization degrees are obtained, and the volume density, electrical conductivity, thermal conductivity, corrosion resistance and mechanical processing properties of the product are improved through graphitization.

[0070] In some of the embodiments, the pressure of the molding process is 150 MPa to 250 MPa, which is conducive to pressing the materials together, making them relatively stable and facilitating subsequent graphitization treatment.

[0071] In some of the embodiments, the temperature of the graphitization treatment is 2500°C to 3000°C, and the time is 15h to 50h, which is beneficial to improving the degree of graphitization of the product. The better the degree of graphitization, the fewer cracks, and the more beneficial it is to improving the performance of the negative electrode sheet and the lithium battery.

[0072] In some embodiments, the carbon source is a coke raw material, and the sulfur content of the coke raw material is less than 5wt%. During the graphitization process, the overflow of sulfur promotes the formation of pores inside the graphite, and controlling the sulfur content of the coke raw material is beneficial to improving the performance of the negative electrode sheet and the lithium battery. Furthermore, the sulfur content of the coke raw material is 1wt% to 5wt%.

[0073] It is understandable that the catalyst described in the present invention is a catalyst conventionally used in the preparation of graphite in the art, and no requirement is made for this. Optionally, the catalyst is ferrosoferric oxide.

[0074] Similarly, the conductive agent used to prepare graphite in the present invention is the conductive agent conventionally used to prepare graphite in the art, and no requirement is made for this. Optionally, the conductive agent used to prepare graphite is conductive carbon black.

[0075] Similarly, the binder used to prepare graphite in the present invention is a binder conventionally used to prepare graphite in the art, and no requirement is made for this. Optionally, the binder used to prepare graphite is asphalt.

[0076] The present invention also provides a negative electrode active material, which includes the graphite as described above.

[0077] The present invention also provides a negative electrode plate, which comprises a negative electrode current collector and a negative electrode active layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active layer comprises the graphite as described above, or the negative electrode active material as described above.

[0078] In some embodiments, the negative electrode active layer further includes a negative electrode conductive agent and a negative electrode binder;

[0079] In terms of mass percentage, the active layer includes 85% to 98% of the negative electrode active material, 0.5% to 10% of the negative electrode conductor, and 1.5% to 5% of the negative electrode binder.

[0080] It can be understood that in the negative electrode active layer, the mass percentage of the negative electrode active material is 85% to 98%, including but not limited to 85%, 90%, 92%, 93%, 94%, 94.5%, 95%, 96%, 97% or 98%; the mass percentage of the negative electrode conductor is 0.5% to 10%, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.6%, 3.8%, 4.0%, 4.5%, 5%, 6%, 7%, 8%, 9% or 10%; and the mass percentage of the negative electrode binder is 1.5% to 5%, including but not limited to 1%, 1.5%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.6%, 3.8%, 4.0%, 4.5% or 5%.

[0081] In some embodiments, the negative electrode conductive agent includes at least one of carbon nanotubes, carbon nanofibers, conductive graphite (SP), graphene, acetylene black and carbon black, which have the advantages of high conductivity and low resistance. Further, the carbon black is selected from at least one of Ketjen black, channel black, furnace black and thermal black.

[0082] In some embodiments, the negative electrode binder includes at least one of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid and polyacrylate. These negative electrode binders can better adhere and retain the negative electrode active material on the current collector, enhance the electronic contact between the negative electrode active material and the negative electrode conductor, and between the negative electrode active material and the current collector, and can better disperse, thicken, suspend, bond and facilitate lithium ion transmission. Further, the negative electrode binder is a mixture of CMC and SBR. Further, the negative electrode binder is composed of CMC and SBR in a mass ratio of 1: (0.5-3.0), including but not limited to 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5, 1:2.8 or 1:3.0.

[0083] In some embodiments, the negative electrode current collector is selected from metal foil or porous metal plate. Further, the negative electrode current collector is metal foil, such as copper foil or aluminum foil, more preferably copper foil.

[0084] In addition, the present invention also provides a method for preparing the above-mentioned negative electrode sheet.

[0085] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps:

[0086] S100: According to the design of the negative electrode sheet, the negative electrode active material, the negative electrode conductive agent and the negative electrode binder are mixed in a solvent to prepare a negative electrode active slurry.

[0087] S200: coating the negative electrode active slurry on the surface of the negative electrode current collector, drying to remove the solvent, preparing a negative electrode active layer, and obtaining a negative electrode sheet.

[0088] The present invention also provides an energy storage device, comprising the graphite as described above, or comprising the negative electrode active material as described above, or comprising the negative electrode plate as described above. It can be understood that the energy storage device described in the present invention has the beneficial effects described in the graphite or negative electrode active material or negative electrode plate as described above, which will not be repeated here, that is, the energy storage device has a higher energy density and better dynamic performance. Without limitation, the energy storage device is a battery. Further, the battery is a lithium-ion battery.

[0089] In one embodiment, the lithium-ion battery is selected from one of a button battery, a soft-pack battery, a square battery and a cylindrical battery.

[0090] In one embodiment, the lithium-ion battery further comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active layer disposed on a surface of the positive electrode current collector;

[0091] The positive electrode active layer includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.

[0092] In some embodiments, the positive electrode current collector is selected from metal foil or porous metal plate. Preferably, the current collector is metal foil, such as copper foil or aluminum foil, more preferably aluminum foil.

[0093] In one embodiment, the positive electrode active material includes lithium iron phosphate (LiFePO 4 ), at least one of lithium manganese oxide, lithium cobalt oxide and lithium titanate.

[0094] In one embodiment, the positive electrode conductive agent includes at least one of acetylene black, graphene, carbon nanotubes and carbon black.

[0095] In one embodiment, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA) and polytetrafluoroethylene (PTFE).

[0096] In some embodiments, the battery further comprises a separator. Optionally, the separator is made of polypropylene (PP) or polyethylene (PE).

[0097] In some embodiments, the battery further comprises an electrolyte.

[0098] It is understandable that the present invention has no special requirements for the electrolyte, and conventional electrolytes in the field of lithium-ion batteries can be used. Without limitation, the solvent in the electrolyte includes ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), propylene carbonate (PC) and diethyl carbonate (DEC). The lithium salt in the electrolyte includes LiPF 6 , LiTFSI, LiBF4, LiBOB and LiDFOB.

[0099] In one embodiment, the solvent in the electrolyte is a mixed solvent of EC, EMC, and DEC in a volume ratio of 1:1:1, and the lithium salt in the electrolyte is LiPF 6 , further, the concentration of lithium salt in the electrolyte is 1 mol / L.

[0100] The present invention also provides a method for preparing a lithium ion battery, comprising the following steps:

[0101] (1) Preparation of positive electrode sheet:

[0102] The positive electrode active material, the positive electrode conductive agent and the positive electrode binder are mixed in a solvent, stirred evenly and then evenly coated on the positive electrode current collector, and dried to obtain a positive electrode sheet. Materials such as metal foil or porous metal plate can be used as the positive electrode current collector. Aluminum foil is preferably used.

[0103] (2) Preparation of negative electrode sheet:

[0104] Providing a negative electrode active slurry, wherein the components of the negative electrode active slurry include a negative electrode active material, a negative electrode conductive agent and a negative electrode binder;

[0105] The negative electrode active slurry is coated on the surface of the negative electrode current collector to form a negative electrode active layer to prepare a negative electrode sheet.

[0106] (3) Preparation of electrolyte:

[0107] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed, and then dry lithium salt is dissolved in the mixed organic solvent to prepare an electrolyte.

[0108] Optionally, the volume ratio of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) is 1:1:1. Optionally, the lithium salt is LiPF 6 , further, the concentration in the electrolyte is 1 mol / L.

[0109] (4) Providing a diaphragm.

[0110] (5) Preparation of batteries:

[0111] The positive electrode sheet, negative electrode sheet, separator and electrolyte are assembled into a battery cell.

[0112] The present invention also provides an electric device, comprising the energy storage device as described above, wherein the energy storage device supplies power to the electric device. It is understandable that the electric device described in the present invention has the beneficial effects described in the graphite or negative electrode active material or negative electrode sheet as described above, which will not be repeated here. Optionally, the electric device may include a plurality of battery packs composed of the lithium-ion batteries described above. Optionally, the electric device may be a lighting fixture, etc.

[0113] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0114] Example 1

[0115] This embodiment provides a graphite and a preparation method thereof, a negative electrode sheet and a preparation method thereof, and a lithium-ion battery and a preparation method thereof, which are specifically as follows:

[0116] (1) Preparation of positive electrode sheet:

[0117] LiFePO 4 SP and PVDF are uniformly dispersed in NMP in a mass ratio of 96.5%:1.7%:1.8%, stirred evenly to form a positive electrode slurry, which is applied to the aluminum current collector and dried to obtain a positive electrode sheet, wherein the surface density is 16.3 mg / cm 2 , compacted density is 2.45g / cm 3 .

[0118] (2) Preparation of negative electrode sheet:

[0119] The mixture of the coking raw material, ferroferric oxide, conductive carbon black and asphalt is molded at a pressure of 250 MPa to prepare a solid composite; the solid composite is graphitized at 2500° C. for 15 h to obtain graphite, which is subsequently used as a negative electrode active material. The particle size distribution of the graphite can be found in Figure 1 , the graphite D50 is 27±2μm, the particle size distribution is a single-peak normal distribution, the degree of graphitization GD is 89%±0.2%, and the GD / D50 is 3.06%~3.88%;

[0120] The negative electrode active material, conductive agent acetylene black, CMC, and SBR were uniformly dispersed in deionized water at a ratio of 96%: 1.2%: 1.0%: 1.8% to form a negative electrode slurry, which was applied to the copper current collector and dried to obtain a negative electrode sheet, wherein the surface density was 8.41 mg / cm 2 , compacted density is 1.5g / cm 3 .

[0121] (3) Preparation of electrolyte:

[0122] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed, and then dry lithium salt is dissolved in the mixed organic solvent to prepare an electrolyte.

[0123] Optionally, the volume ratio of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) is 1:1:1. Optionally, the lithium salt is LiPF 6 , further, the concentration in the electrolyte is 1 mol / L.

[0124] (4) providing a diaphragm;

[0125] (5) Battery assembly:

[0126] The positive and negative electrode sheets are subjected to processes such as electrode sheet rolling, die cutting, striping, assembly, baking, liquid injection, formation, and aging to form battery cells.

[0127] Example 2

[0128] This embodiment is basically the same as embodiment 1, except that: during the preparation of graphite, the pressure of the molding process is 150MPa and 250MPa, the temperature of the graphitization process is 2500℃ and 3000℃, the time is 25h and 50h, and the final graphite particle size distribution is different. After two different particle size graphites are physically dry mixed, the graphite particle size distribution obtained in this embodiment is shown in FIG. Figure 1 The graphite D50 particle size is 23±2μm, the particle size distribution is bimodal (the peak value of the first peak is 10μm, the peak value of the second peak is 26μm, and the peak area ratio of the first peak to the second peak is 2:8), the degree of graphitization GD is 89%±0.2%, and GD / D50 is 3.35%~4.25%.

[0129] Example 3

[0130] This embodiment is basically the same as embodiment 1, except that: during the preparation of graphite, the pressure of the molding process is 150MPa and 250MPa, the temperature of the graphitization process is 2500℃ and 3000℃, the time is 25h and 50h, and the final graphite particle size distribution is different. After two different particle size graphites are physically dry mixed, the graphite particle size distribution obtained in this embodiment is shown in FIG. Figure 1 The graphite D50 particle size is 20±2μm, the particle size distribution is a bimodal distribution (the peak value of the first peak is 10μm, the peak value of the second peak is 26μm, and the peak area ratio of the first peak to the second peak is 5:5), the degree of graphitization GD is 89%±0.2%, and GD / D50 is 4.03%~4.96%.

[0131] Example 4

[0132] This embodiment is basically the same as embodiment 1, except that: during the preparation of graphite, the pressure of the molding process is 150MPa and 250MPa, the temperature of the graphitization process is 2500℃ and 3000℃, the time is 25h and 50h, and the final graphite particle size distribution is different. After two different particle size graphites are physically dry mixed, the graphite particle size distribution obtained in this embodiment is shown in FIG. Figure 1 The graphite D50 particle size is 10±2μm, the particle size distribution is a bimodal distribution (the peak value of the first peak is 10μm, the peak value of the second peak is 26μm, and the peak area ratio of the first peak to the second peak is 1:9), the degree of graphitization GD is 89%±0.2%, and GD / D50 is 7.4%~11.15%.

[0133] Example 5

[0134] This embodiment is basically the same as Example 1, and is different from Example 1 in that: during the preparation of graphite, the pressure of the molding treatment is 150MPa and 250MPa, the temperature of the graphitization treatment is 2500°C and 3000°C, the time is 25h and 50h, and the final graphite particle size distribution is different. After two different particle size graphites are physically dry mixed, the graphite particle size distribution of this embodiment is shown in Table 2, the graphite D50 particle size is 15±2μm, the particle size distribution is a bimodal distribution (the peak value of the first peak is 8μm, the peak value of the second peak is 30μm, and the peak area ratio of the first peak to the second peak is 5:5), the degree of graphitization GD is 89%±0.2%, and GD / D50 is 5.22%~6.86%.

[0135] Example 6

[0136] This embodiment is basically the same as embodiment 1, except that: during the preparation of graphite, the pressure of the molding process is 150MPa and 250MPa, the temperature of the graphitization process is 2500℃ and 3000℃, the time is 25h and 50h, and the final graphite particle size distribution is different. After two different particle size graphites are physically dry mixed, the graphite particle size distribution obtained in this embodiment is shown in FIG. Figure 1 The graphite D50 particle size is 23±2μm, the particle size distribution is bimodal (the peak value of the first peak is 12μm, the peak value of the second peak is 34μm, and the peak area ratio of the first peak to the second peak is 2:8), the degree of graphitization GD is 93%±0.2%, and GD / D50 is 3.71%~4.43%.

[0137] Comparative Example 1

[0138] This embodiment is basically the same as embodiment 1, except that: during the preparation of graphite, the pressure of the molding treatment is 350 MPa, the temperature of the graphitization treatment is 3500°C, and the time is 60 h. The particle size distribution of the final graphite is different. The particle size distribution of the graphite in this embodiment is shown in Figure 1 The graphite D50 particle size is 8±2μm, the particle size distribution is a unimodal normal distribution, the degree of graphitization GD is 96%±0.2%, and the GD / D50 is between 9.58% and 16.03%.

[0139] test:

[0140] The battery cycle performance of the above embodiments and comparative examples was investigated:

[0141] The charge and discharge performance and cycle performance test process test conditions are shown in Table 1, and the test results are shown in Table 2.

[0142] Table 1

[0143]

[0144] It can be understood that 1000 cls means 1000 cycles, that is, 1000 cycles.

[0145] 1000 cls capacity retention rate (%) = 1000th cycle discharge capacity / initial discharge capacity (i.e. first discharge capacity × 100%).

[0146] like Figure 2 As shown, the battery cycle performance results of Comparative Example 1 and Example 3 are shown.

[0147] Table 2

[0148]

[0149] It should be noted that, due to measurement errors, D10, D25, D50, D75 and D90, as well as the degree of graphitization GD provided in Examples 1 to 6 and Comparative Example 1 are all expressed as ranges, and the respective GD / D50 values ​​can be obtained by calculation.

[0150] From Table 2 and Figure 2 It can be seen that the large-particle-size and low-graphitization-degree graphite in the examples has an optimization effect on improving the performance in the later stage of the cycle (compared with the small-particle-size and high-graphitization-degree graphite in comparative example 1), among which the improvement effect of example 3 is the most obvious.

[0151] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0152] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the attached claims described in the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.

Claims

1. A graphite, characterized in that: Its D50 is 8μm to 35μm, and its particle size distribution has a single peak or a double peak; The graphite has a graphitization degree of GD, GD is 88% to 95%, and GD / D50 is 2.6% to 11.5%.

2. The graphite according to claim 1, characterized in that GD / D50 is 3.0%~5.5%.

3. The graphite according to claim 1, characterized in that The graphitization degree of the graphite is negatively correlated with its particle size.

4. The graphite according to any one of claims 1 to 3, characterized in that The particle size distribution of the graphite is a unimodal normal distribution, the D10 of the graphite is 10 μm to 15 μm, the D50 is 25 μm to 29 μm, and the D90 is 40 μm to 50 μm.

5. The graphite according to any one of claims 1 to 3, characterized in that The particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5): (5-9); The graphite has a D10 of 6 μm to 8 μm, a D25 of 8 μm to 12 μm, a D50 of 12 μm to 20 μm, a D75 of 20 μm to 40 μm, and a D90 of 40 μm to 50 μm.

6. The graphite according to any one of claims 1 to 3, characterized in that The particle size distribution of the graphite is a bimodal distribution, wherein the peak value of the first peak is 10 μm, the peak value of the second peak is 26 μm, and the peak area ratio of the first peak to the second peak is (1-5): (5-9); The graphite has a D10 of 6 μm to 8 μm, a D25 of 8 μm to 10 μm, a D50 of 10 μm to 15 μm, a D75 of 15 μm to 30 μm, and a D90 of 30 μm to 50 μm.

7. A method for preparing graphite according to any one of claims 1 to 6, characterized in that: The steps include: The mixture of the carbon source, the catalyst, the conductive agent and the binder is subjected to a molding process to prepare a solid composite; The solid composite is graphitized, and the graphite is prepared by controlling the temperature and time of the graphitization treatment.

8. A negative electrode active material, characterized in that: The invention comprises the graphite as claimed in any one of claims 1 to 6.

9. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active layer comprises the graphite according to any one of claims 1 to 6, or the negative electrode active material according to claim 8.

10. The negative electrode sheet according to claim 9, characterized in that: The negative electrode active layer also includes a negative electrode conductive agent and a negative electrode binder; In terms of mass percentage, the active layer includes 85% to 98% of the negative electrode active material, 0.5% to 10% of the negative electrode conductor, and 1.5% to 5% of the negative electrode binder.

11. The negative electrode sheet according to claim 10, characterized in that: Satisfy at least one of the following (1) to (2): (1) The negative electrode conductive agent includes at least one of carbon nanotubes, carbon nanofibers, conductive graphite, graphene, acetylene black and carbon black; (2) The negative electrode binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid and polyacrylate.

12. An energy storage device, characterized in that: It comprises the graphite according to any one of claims 1 to 6, or the negative electrode active material according to claim 8, or the negative electrode sheet according to any one of claims 9 to 11.

13. An electrical equipment, characterized in that: It includes the energy storage device as described in claim 12, and the energy storage device supplies power to the electrical equipment.

Citation Information

Cited By

  • Negative electrode dynamics rapid assessment method

    CN121656081A